2003
DOI: 10.1097/00126334-200308150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir Plasma Concentrations and Changes in Lipid Levels During Salvage Therapy with Lopinavir/Ritonavir-Containing Regimens

Abstract: In patients receiving salvage therapy with LPV/r, there is an association between LPV plasma concentrations and lipid changes. Patients achieving higher LPV trough concentrations may be at greater risk of experiencing dyslipidemia. Further investigations are warranted to support a direct cause and effect relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 18 publications
2
60
3
Order By: Relevance
“…For some antiretroviral drugs, increased levels in plasma have been shown to be associated with increased toxicity (6,11,12,15).…”
mentioning
confidence: 99%
“…For some antiretroviral drugs, increased levels in plasma have been shown to be associated with increased toxicity (6,11,12,15).…”
mentioning
confidence: 99%
“…They found a positive correlation between the percentage increase in triglycerides and LPV trough levels, but no correlation was found between LPV trough levels and the percentage of increase in cholesterol levels. 12 In a small population all patients with higher LPV trough (especially trough levels > 8 g/mL) levels were the ones at risk of dyslipidaemia [16,17]. Moreover, in a population of 142 ART-experienced patients high triglycerides were found in subjects with high LPV residual concentrations [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that this dyslipidaemia is multifactorial and includes a direct effect of the PI and a more complex mechanism involveing immunologic, genetic and pharmacodynamic factors and HIV-infection itself [5,12,16,17,24]. To our knowledge this is the first prospective study analysing LPV levels with serum lipids in a cohort of only antiretroviral therapy-naive patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It has been suggested that concentrations of lopinavir below 1000 ng/mL are not adequate for suppression of wild-type virus, 8 and although studies have not provided a cut-off value, there have been positive correlations between lipid profiles 9 and liver enzyme elevation 10 and lopinavir pharmacokinetics. There is currently a lack of pharmacokinetic data in HIVinfected pregnant women and as such 'therapeutic' levels of lopinavir are based on data obtained from a Caucasian male cohort (University of Liverpool, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Days on LPV/r at sampling 19 Hours since last dose 12 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) VL at trough sampling (copies/mL) 182 (40-252,000)…”
Section: Details Of Tdm Samples Median (Range)mentioning
confidence: 99%